2002
DOI: 10.1021/ci025569t
|View full text |Cite
|
Sign up to set email alerts
|

Similarity Metrics for Ligands Reflecting the Similarity of the Target Proteins

Abstract: In this study we evaluate how far the scope of similarity searching can be extended to identify not only ligands binding to the same target as the reference ligand(s) but also ligands of other homologous targets without initially known ligands. This "homology-based similarity searching" requires molecular representations reflecting the ability of a molecule to interact with target proteins. The Similog keys, which are introduced here as a new molecular representation, were designed to fulfill such requirements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(164 citation statements)
references
References 36 publications
4
159
0
1
Order By: Relevance
“…There is, however, an alternative approach to data fusion that was first suggested by Xue et al [38] and by Schuffenhauer et al [68]. This approach, which we refer to as group fusion, can be used when several, structurally-diverse reference structures are available, as may be the case from analysis of published competitor compounds or from the hits in an HTS experiment.…”
Section: Combination Of Rankings Using Group Fusionmentioning
confidence: 99%
“…There is, however, an alternative approach to data fusion that was first suggested by Xue et al [38] and by Schuffenhauer et al [68]. This approach, which we refer to as group fusion, can be used when several, structurally-diverse reference structures are available, as may be the case from analysis of published competitor compounds or from the hits in an HTS experiment.…”
Section: Combination Of Rankings Using Group Fusionmentioning
confidence: 99%
“…However, search performance usually improves when multiple active compounds are available. Accordingly, various approaches have been introduced to utilize multiple reference molecules in fingerprint calculations, including consensus 9 or centroid 10 fingerprints, scaling procedures, 11 and nearest-neighbor methods 10,12 (i.e., data fusion techniques). Several studies have been conducted to compare these different search strategies, and nearestneighbor as well as centroid calculations were often found to perform best.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to compare these different search strategies, and nearestneighbor as well as centroid calculations were often found to perform best. 10,12 The relative performance of these search strategies is often influenced by differences in structural diversity between compound classes. For example, for structurally homogeneous classes, the 1-NN approach easily detects active compounds, whereas averaging of fingerprints or similarity values often produces better results than 1-NN for moderately diverse classes.…”
Section: Introductionmentioning
confidence: 99%
“…The first detailed study of this type was by Willett and Winterman [12], who found that computed molecular similarities could be used to predict a range of physical, chemical and biological properties in a range of small datasets for which both structural and property information were available. There have been many subsequent examples of this approach to the evaluation of similarity procedures [13][14][15][16][17], and further supporting evidence for the general applicability of the Principle comes from studies in chemogenomics [18][19][20][21]. It must be emphasized that there are many exceptions to the Principle [22,23], but it has been found to provide a very useful basis for the development of a range of similarity-based approaches for the processing of large chemical databases.…”
Section: Computing Molecular Similarities the Similar Property Principlementioning
confidence: 99%